Bilateral erector spinae plane block provides postoperative analgesia for laparoscopic distal esophagectomy surgery - Çiftçi, Bahadır; Ekinci, Mürsel (Springer, 2019)
The ultrasound-guided erector spinae plane block (ESPB) is a newly described interfascial plane block that provides both thoracic analgesia at T5 level and abdominal analgesia at T7–9 level (Restrepo Garces et al. 2017). Thus, ESPB may be a good alternative to other invasive techniques such as epidural analgesia in the postoperative analgesia treatment following abdominal operations. In this case report, we would like to report our successful ESPB experience for postoperative pain management after distal esophagectomy and proximal gastrectomy surgery.
WOS: 000468131800001
Keywords: Bilateral Erector; Spinae Plane Block; Laparoscopic Distal; Esophagectomy Surgery